Strategic Brand Management and Customer Loyalty in Jamaica - Rabbarts, Henry (Journal of Strategic Management, 2024)
Purpose: The aim of the study was to assess the strategic brand management and customer loyalty in Jamaica. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that a well-managed brand strategy involves consistent brand messaging, high-quality products or services, and an emotional connection with customers. Effective brand management ensures that a brand's values align with those of its target audience, fostering trust and long-term loyalty. Additionally, customer engagement through personalized experiences and responsive customer service enhances loyalty by making customers feel valued and understood. Companies that excel in strategic brand management often leverage data analytics to refine their strategies, ensuring that they meet evolving customer needs and preferences. Ultimately, the synergy between strategic brand management and customer loyalty results in a competitive advantage, higher customer retention rates, and increased lifetime customer value. Implications to Theory, Practice and Policy: Brand equity theory, social identity theory and relationship marketing theory may be used to anchor future studies on assessing the strategic brand management and customer loyalty in Jamaica. In practical implementation, businesses should adopt omni-channel brand communication strategies to ensure consistent and engaging brand messages across all customer touchpoints. Advocating for policies that prioritize consumer protection, data privacy, and ethical marketing practices is essential for building trust and confidence among consumers.